Serwisy internetowe rządowej administracji skarbowej - Gadomski, Sebastian (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the contents of Web pages of revenue administration and the dynamic of viewing in time partition from January to October 2005. The author presents also suggestions concerning enlargement of information supply in internet services of revenue administration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 287-295